Examining the link between bullying participation, psychopathy and empathy in a large retrospective sample of university students - Walsh, Jeffrey A. (Criminal justice studies, 2018)
School bullying has strong empirical links to a broad range of adverse psychosocial outcomes including depression, eating disorders, early abuse of alcohol and drugs, self-injury, poor academic performance, and low self-esteem. Bullying has been implicated in infamous school shootings and numerous youth suicides. This work extends prior studies examining four categories of bullying participation, employing standardized scales measuring psychopathy and empathy, to better understand bullying participation roles and social cognition. The study includes a gender-based examination. Findings indicate males and females engage and experience bullying differently. The present retrospective self-report descriptive study consists of a large university sample (n = 2113), an underutilized population in the bullying literature, reflecting on their bullying experiences in high school. Findings contribute to current knowledge about the interrelationship between bullying participation, empathy and psychopathy. Results show significant differences across participation categories and by gender. Specific results emphasize deficits in primary psychopathy among both male and female victims. Victims of bullying may lack a healthy/self-preservation baseline of primary psychopathy. Intervention and prevention efforts geared towards bullies remain important, but a more holistic approach inclusive of victims, facilitating normal/healthy narcissism, self-esteem building, and greater capacity to deal with their social environment is likely to be most effective.